Number-Theoretic Attack on Lyuu-Wu's Multi-proxy Multi-signature Scheme - Fanyu Kong; Jia Yu (2009 fifth International Conference on Information Assurance and Security : 18-20 August 2009, 2009)
Y. D. Lyuu and M. L. Wu had proposed an improved multi-proxy multi-signature scheme, which was claimed to resist the forge attack. Lately, L. Guo and G. Wang found an inside attack on the Lyuu-Wu's scheme. In this paper, we propose a new attack on Lyuu-Wu's scheme, which can factor the parameter N and Q by using efficient number-theoretic algorithms when Q is roughly larger than the square root of N. It follows that Lyuu-Wu's scheme suffers from the forge attack from the proxy signers in that case.